STAD Cooperative Model with Audio Visual Media Assistance as an Effort to Improve Elementary Madrasah Students' Learning Achievement: A Classroom Action Research - Listiana (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning achievement by using the STAD type cooperative learning model assisted by audio-visual media. This study is a classroom action research with four stages, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data were collected using observation and test techniques. The data obtained were analyzed using descriptive statistical techniques. The results of the study indicate that the STAD type cooperative learning model assisted by audio-visual can improve student learning achievement. Therefore, this audio-visual media-assisted cooperative model can be used as an alternative in overcoming the low learning achievement of elementary school students.